Preferred information sources and needs of cancer patients on disease symptoms and management: a cross-sectional study - Mekuria AB; Erku DA; Belachew SA (Patient Preference and Adherence, 2016)
Abebe Basazn Mekuria,1 Daniel Asfaw Erku,2 Sewunet Admasu Belachew3 1Department of Pharmacology, 2Department of Pharmaceutical Chemistry, 3Department of Clinical Pharmacy, School of Pharmacy, University of Gondar, Gondar, Ethiopia Purpose: This study aimed at identifying the information needs of cancer patients, their preferences for the means of receiving health information, and the perceived level of satisfaction of existing possibilities for acquiring cancer-related information in Ethiopia.Materials and methods: An institutional-based cross-sectional survey was employed on 556 cancer patients undergoing chemotherapy in the oncology wards of Gondar University Referral Hospital and Tikur Anbesa Specialized Hospital. Data were collected through interviewer-administered questionnaire.Results: The principal information regarded as the most important by the majority of them (67.26%) concerned information on the specific type of cancer (name and stage of cancer), followed by the side effects of chemotherapy and their management (63.29%) and “prognosis (survival)” (51.8%). Doctors were the overwhelming information source about cancer (88.8%), followed by nurses (34%). The majority of respondents (70.3%) were not satisfied at all or satisfied a little, while 15.6% of respondents reported that they were “quite” or “very” satisfied with the existing possibilities for acquiring information regarding cancer.Conclusion: Medical practitioners other than doctors and nurses such as clinical pharmacists should support and identify measures that can enhance patients’ satisfaction level regarding the existing possibilities for acquiring information regarding cancer. Periodic assessment of cancer patient’s information requirements is also crucial, considering the ever-changing dynamics of priorities of such information desires. Keywords: information seeking, preference, cancer, Ethiopia